Checklist of Riparian Vegetation Potentially as Phytoremediators in the Upper Gajah Wong River, Yogyakarta - Yusuf, Muhammad; Kurniawan, Wisnu; Listianto, Listianto; Afrianto, Mustofa; Urachman, Ziar zia (Proceeding International Conference on Science and Engineering, 2019)
This study aims to determine the types of plants in the upper reaches of the Gajah Wong river which have the potential as phytoremediation agents and provide information about the function of riparian ecosystems. Plant sampling was carried out in December 2016 in three villages namely Sardonoharjo, Hargobinangun and Widomartani. The method used in this research is the transect and plot method. Transect measuring 200 meters according to the shape of the river and paired with a plot of 10 meters long, so that in each location there are 5 plots on the left and right of the river. Inventaritation of vegetation at the river level conducted in three villages upstream of Gajah Wong river found 84 types of plants consisting of 28 types of floor plants (herbs), 23 types of bush plants, 13 types of shrubs, and 21 species of trees. Whereas for phytoremidiator agents 30 plants were found that were able to reduce pollutants based on previous research. The village that has the highest diversity is Wedomartani and Sadonoharjo villages with 41 plant species. Whereas for Hargobinangun village where the place is higher, only 37 species of plants are found.